(untitled) (Research, Society and Development, 2022)
The objective of the study is to identify the relevance of nutrition in the wound healing process in diabetic patients and their topical assistance. The present study is an integrative literature review, which consists of methodological approaches. It was carried out in the period of December 2022, the databases used were the Latin American and Caribbean Literature in Health Sciences and the Nursing Database, using the Health Sciences Descriptors, namely “Food, Diet and Nutrition”, “Healing” and “Diabetes Mellitus”. Then, the quantity of 8 articles was selected to compose the corpus of analysis of eligible articles. Studies concluded that the concentrations of their studied nutrients correlated with healing or that the supplements improved the healing of foot ulcers. That is, a better understanding of the mechanism of action of nutritional supplements can contribute to future protocols and guidelines for the treatment of foot ulceration, with the aim of adding to wound care in an integrated way, considering food, supplementation plus topical care specific. The association between the nutritional status of the patient with a peripheral lesion directly influences the injuries and treatment of the lesions, thus, the clinical look at possible nutritional deficiencies and inflammatory markers promotes a better therapeutic approach.